2021
DOI: 10.2478/helm-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis infection in Ethiopia: systematic review and meta-analysis on prevalence and diagnostic methods

Abstract: SummaryStrongyloides stercoralis is a helminthic intestinal parasite that causes the disease strongyloidiasis. Its prevalence is high in tropics and sub-tropics due to poor sanitation and hygiene. However, its true prevalence is not well known in Ethiopia as most health institutions use low sensitive diagnostic methods. This review aimed to determine the pooled prevalence of S. stercoralis at country, and regional state levels. Papers published on S. stercoralis in Ethiopia from 2010 to 2020 were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Systematic reviews and meta-analyses identified STH burden [ 27 30 , 41 , 43 , 61 , 62 ]. In five studies, the prevalence of STH in Ethiopia ranged from 13 to 52.4% [ 27 30 , 39 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews and meta-analyses identified STH burden [ 27 30 , 41 , 43 , 61 , 62 ]. In five studies, the prevalence of STH in Ethiopia ranged from 13 to 52.4% [ 27 30 , 39 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The burden of parasite among pregnant women was 29% in Ethiopia [ 43 ]. Furthermore, the prevalence of Strongyloides stercoralis in Ethiopia ranged from 1.8 to 11.1% in adults [ 61 , 62 ], from 0.3 to 20.7% in children, and 1.5 to 17.3% in HIV-positive adults [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation